2012
DOI: 10.1029/2011jb008257
|View full text |Cite
|
Sign up to set email alerts
|

Magma sources involved in the 2002 Nyiragongo eruption, as inferred from an InSAR analysis

Abstract: along a 20 km-long fracture network extending from the volcano to the city of Goma. The event was captured by InSAR data from the ERS-2 and RADARSAT-1 satellites. A combination of 3D numerical modeling and inversions is used to analyze these displacements. Using Akaike Information Criteria, we determine that a model with two subvertical dikes is the most likely explanation for the 2002 InSAR deformation signal. A first, shallow dike, 2 km high, is associated with the eruptive fissure, and a second, deeper dike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 86 publications
4
88
0
Order By: Relevance
“…In addition, rift-wide extension, detected by InSAR, together with seismicity was interpreted in terms of a southward propagating shallow dyke and a deeper one, 40 km long (Wauthier et al, 2012). Wadge and Burt (2011) argued that a very similar N-S dyke-driven eruption occurred during the only other historical flank eruption in 1977.…”
Section: Nyiragongo (2002)mentioning
confidence: 99%
“…In addition, rift-wide extension, detected by InSAR, together with seismicity was interpreted in terms of a southward propagating shallow dyke and a deeper one, 40 km long (Wauthier et al, 2012). Wadge and Burt (2011) argued that a very similar N-S dyke-driven eruption occurred during the only other historical flank eruption in 1977.…”
Section: Nyiragongo (2002)mentioning
confidence: 99%
“…In our model, we assume that the convective magma (which could represent between 300 and 1700 × 10 6 m 3 by 2022) is in part emplaced within a magma chamber, while the other part is intruded into dykes. Wauthier et al [2012] suggest that the deep, slowly filling dyke is situated either under the city of Goma or part of another slowly filling dyke system. They suggest that the deep dyke they inferred might be too narrow to cause detectable InSAR displacements.…”
Section: 1002/2013jb010895mentioning
confidence: 99%
“…The last eruption (January 2002) has shown that while only a small part of the lava lake erupted (less than 10%), a much larger amount of magma intruded into dykes, representing a significant volcanic hazard if a catastrophic fissural eruption similar to 2002 were to be repeated [Favalli et al, 2009;Wauthier et al, 2012]. Thus, even if the lava lake volume is predicted to range within 10 to 15 × 10 6 m 3 for the next decade, it does not reduce the risk of lava flows within the city of Goma.…”
Section: 1002/2013jb010895mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the platforms inside the crater (P3), the deepest, is varying of several tens of meters a year due to the presence of a very active lava lake [4]. The flanks of the crater are so steep that classical phase unwrapping always fails connecting P3 to the surrounding, preventing a correct height measurement of the platform to be made.…”
Section: Introductionmentioning
confidence: 99%